2010
DOI: 10.1007/s10722-009-9525-0
|View full text |Cite
|
Sign up to set email alerts
|

Microsatellite genotyping of apple (Malus × domestica Borkh.) genetic resources in the Netherlands: application in collection management and variety identification

Abstract: A highly informative set of 16 microsatellite markers was used to fingerprint 695 apple accessions from eight Dutch collections. Among the total sample, 475 different genotypes were distinguished based on multi-locus microsatellite variation, revealing a potential redundancy within the total sample of 32%. The majority of redundancies were found between collections, rather than within collections. No single collection covered the total observed diversity well, as each collection consisted of about 50% of uniqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
52
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(63 citation statements)
references
References 27 publications
7
52
2
Order By: Relevance
“…Identical microsatellite profiles of cvs Mantet and Glencross could be due to mistake in the reported pedigree or potential documentation error. Similar results were published for known pedigrees (Evans et al 2011) or incorrect documented cultivar names (van Treuren et al 2010) in apple collections using SSR markers. Therefore for apple, microsatellite genotyping appeared a very efficient tool for enhancing collection management of genetic resources and for cultivar identification.…”
Section: Resultssupporting
confidence: 84%
See 2 more Smart Citations
“…Identical microsatellite profiles of cvs Mantet and Glencross could be due to mistake in the reported pedigree or potential documentation error. Similar results were published for known pedigrees (Evans et al 2011) or incorrect documented cultivar names (van Treuren et al 2010) in apple collections using SSR markers. Therefore for apple, microsatellite genotyping appeared a very efficient tool for enhancing collection management of genetic resources and for cultivar identification.…”
Section: Resultssupporting
confidence: 84%
“…The dendrogram showed that there was a genotype dependence on pedigree and origin of apple cultivars (Table 1). Therefore SSR markers were useful for parentage study (Kitahara et al 2005;Evans et al 2011) and cultivar identification (Galli et al 2005;van Treuren et al 2010) of apple genotypes. The first group (I.)…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The identification of duplicates on germplasm banks of vegetatively propagated plants seems to be common (Irish et al 2010;van Treuren et al 2010). This may be due to usual exchanges of propagules among farmers of different regions, especially when the species has economical importance.…”
Section: Discussionmentioning
confidence: 99%
“…Microsatellite markers, due to high information generated per locus, have been used to identify duplicates on germplasm banks and populations of different species (Robichaud et al 2006;Irish et al 2010;van Treuren et al 2010). Methods of identification that use multiloci profiles of microsatellites are more accurate than the ones based on dominant markers, since genotypes can present a complete coincidence and the probability of casual coincidence can be measured based on allelic frequencies (Paetkau and Strobeck 1994).…”
Section: Introductionmentioning
confidence: 99%